The effect of financial technology, online shopping, and self-control on consumptive behavior - Tina Sulistiyani; Ariharaan Muthusamy; Ahmad Rizal Solihudin (Jurnal Fokus Manajemen Bisnis, 2023)
Technological advancements have now been felt in business, particularly in financial services companies. The financial services industry innovates in financial services, namely building financial technology. This study aims to determine the influence of financial technology, online shopping, and self-control on the consumptive behavior of Generation Z in Yogyakarta. The sample in this study was 520 respondents taken by sampling technique using non-probability sampling with purposive sampling method. The data obtained is then processed using the Smart PLS statistical tool. The results showed that online shopping had a negative influence on consumptive behavior, while financial technology and self-control showed a positive impact on consumptive behavior.